C# 2010 for programmers - Deitel, Paul (Prentice Hall, 2011)
Introduction; Dive IntoÂ® Visual C# 2010 Express; Introduction to C# Applications; Introduction to Classes and Objects; Control Statements: Part 1; Control Statements: Part 2; Methods: A Deeper Look; Arrays; Introduction to LINQ and the List Collection ; Classes and Objects: A Deeper Look; OOP: Polymorphism, Interfaces and Operator Overloading;...